دور حوكمة الشركات في الحد من ممارسات المحاسبة الابداعية - شريط, ابتسام; رزاق لبزة, خلود; شريف حضرية, سارة (My University, 2017)
This study aimed to figure out and highlight the role and effectiveness of corporate governance in the limitation of the creative accounting practices , the study depended on descriptive analytical method , to achieve the study objectives we have set up and distributed (50) questionnaire on the study population which consisted of …….auditors and accountants . After receiving questionnaires (44 valid ones) we have analyzed them by using SPSS program and Excel 2010 . The study revealed a statistically significant role of the application of corporate governance in reducing the negative impact of creative accounting on the reliability of the financial statements . This main result was concluded through a group of secondary results that confirmed the role of different corporate governance principles on the aforementioned role .
مذكرة ماستر تدقيق محاسبي
Keywords: حوكمة الشركات ، المحاسبة الابداعية، ادارة المخاطر، ادارة الارباح; corporate governance , creative accounting , risk management